2006
DOI: 10.1038/sj.leu.2404183
|View full text |Cite
|
Sign up to set email alerts
|

Richter's and prolymphocytic transformation of chronic lymphocytic leukemia are associated with high mRNA expression of activation-induced cytidine deaminase and aberrant somatic hypermutation

Abstract: Chronic lymphocytic leukemia (CLL) is an indolent B-cell nonHodgkin's lymphoma that may transform into higher-grade lymphoma. The transformation involves an increased number of prolymphocytic cells, termed prolymphocytic transformation (PLT) or the development of diffuse large B-cell lymphoma (DLBL), also referred to as Richter's transformation (RT). To analyze whether activation-induced cytidine deaminase (AID), which is essential for somatic hypermutation (SHM) of normal B-cells, and malfunction of SHM terme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Because frequency of mutations and AID protein/RNA expression are both lower in MALT lymphomas, one might speculate an active involvement of ASHM in the high-grade transformation process of MALT lymphoma to overt DLBCL, resembling that described for Richter and prolymphocytic transformation in chronic lymphocytic leukemia. 25 By mutating regulatory and coding sequences of the targeted genes, ASHM may represent a major contributor to their pathogenesis. Images were captured with a Leica DMLB microscope (Leica, Bensheim, Germany) using a Leica PL FLUOTAR objective lens (40ϫ/0.70) and a Leica DC200 camera.…”
Section: Resultsmentioning
confidence: 99%
“…Because frequency of mutations and AID protein/RNA expression are both lower in MALT lymphomas, one might speculate an active involvement of ASHM in the high-grade transformation process of MALT lymphoma to overt DLBCL, resembling that described for Richter and prolymphocytic transformation in chronic lymphocytic leukemia. 25 By mutating regulatory and coding sequences of the targeted genes, ASHM may represent a major contributor to their pathogenesis. Images were captured with a Leica DMLB microscope (Leica, Bensheim, Germany) using a Leica PL FLUOTAR objective lens (40ϫ/0.70) and a Leica DC200 camera.…”
Section: Resultsmentioning
confidence: 99%
“…Here, it might trigger disease progression and even transformation into aggressive lymphoma. Therefore, PC B cells might represent the initiator cells of prolymphocytic or Richter transformation as Reiniger et al 35 indeed found an elevated AID mRNA level in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that AID may have a dual role; initiating chromosomal translocations on one hand and generating secondary hits by mutagenesis on the other (Perez-Duran et al, 2007). Aberrant SHM and involvement of AID were reported to be involved in mutations of TP53 (Malcikova et al, 2008), MYC, PAX5 and RhoH (Reiniger et al, 2006). Moreover, AID activity has been linked to the generation of DSBs involved in translocations in both IG and non-IG loci (Gostissa et al, 2011).…”
Section: Shm Csr and Aid-mediated Dsbmentioning
confidence: 99%